Kekuatan Lentur Glued Laminated (Glulam) Kayu Vertikal dan Horizontal dengan Metode ”Transformed Cross Section” The Bending Strength of Vertical and Horizontal Glued Laminated Timber by ”Transformed Cross Section” Method - I. Sulistyawati; N Nugroho; S Surjokusmo; Y S Hadi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2008)
The bending strength of glued laminated (glulam) timber whose laminas were arranged horizontally will differ from vertically arranged. The important difference was known and used as consideration in lamina arrangement of glulam beam. The determination of precise lamina arrangement will result in maximal strength of design. The aim of this research was to analyze the strength or bending stress in each layer of lamina including maximum stress or modulus of rupture (MOR) of horizontal or vertical glulam beam. The analysis was conducted by using "Transformed Cross Section Area" method. Each glulam represented lamina formation from two wood species with higher modulus of elasticity (MOE) from Kempas (Koompassia malaccencis Maing) and lower one from Borneo (Mixed Species). Lamina with higher level of MOE was arranged in upper and lower edge for horizontal glulam, right and left edge for vertical glulam beam. Lamina with lower MOE was arranged in the middle of the beam. The comparison of higher to lower MOE of lamina was around 1.50 up to 1.70. Epoxy EWA-120 as synthetic adhesive was used with 150 g/m2 glue spread. The result of laboratory examination of both glulam types showed that the average maximum load of vertical glulam was 13.53% higher than horizontal glulam beam, and also MOR of vertical glulam was around 27% higher than horizontal glulam beam. Based on The transformed cross section area method, nominal strength of horizontal glulam has linear function at the entire height. The actual strength that happened at lamina of horizontal glulam beam with lower MOE was smaller than nominal strength. The actual strength that happened at symmetrically vertical glulam beam at its height direction was maximal at the uppers and the lowest side, while it was zero at neutral line.